Penyesuaian Perkawinan, Subjective Well Being dan Konflik Perkawinan - Christina, Dessy; Matulessy, Andik (Persona:Jurnal Psikologi Indonesia, 2016)
The purpose of this study was to examine the relationship between maritaladjustment and subjective well being with marital conflicts Research retrieve datathrough a questionnaire given to 40 couples (80 subjects) with the marriage between 5-10 years of age, have children and live together without any other family in thehousehold, such as parents or in-laws, or other relatives who are also factors thatintervene in the conflict. The result of multiple regression analysis found the value of F =7.422; R = 0.402; p = 0.001 (p <0.01), yangmembuktikan that marital adjustment andsubjective well-beingmemiliki significant correlation with marital conflicts. It found thatthe marital adjustment and subjective well-being able to contribute negatively to themarital conflicts of 16.2%. Results of correlation between marital adjustment withmarital conflict obtained by t = -3.122; r = -0.334; p = 0.003 (p <0.05), which showed asignificant negative correlation between marital adjustment with marital conflicts.Factor subjective well being with marital conflict obtained value t = -2.636; r = -0.288;p = 0.010 (p <0.05), which means it has proved the existence of a significant negativecorrelation between subjective well being with marital conflicts.Keywords : marital adjustment, subjective well-being, marital conflict